Market timing using combined forecasts and machine learning. (25th May 2020) - Mascio, David A.; Fabozzi, Frank J.; Zumwalt, J. Kenton
Abstract: Successful market timing strategies depend on superior forecasting ability. We use a sentiment index model, a kitchen sink logistic regression model, and a machine learning model (least absolute shrinkage and selection operator, LASSO) to forecast 1‐month‐ahead S&P 500 Index returns. In order to determine how successful each strategy is at forecasting the market direction, a "beta optimization" strategy is implemented. We find that the LASSO model outperforms the other models with consistently higher annual returns and lower monthly drawdowns.